The Palgrave Handbook of Religion, Health and Development in Africa - Kilonzo, Susan M.; Chitando, Ezra (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
Approx. 1000 p. 20 illus., 10 illus. in color.